Semiological Orchestrates and their Philosophical Linguistic Effects in Aesthetical Literal Hermeneutics - Teama , AbdalRahman Mohammad; Hassanein, Mohamed Mostufe Ali (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to test the centrality of the sign in interpreting signifiers and signifieds, and the impact of the displacement of signs between minds and objects on the aesthetic reception of the text, regardless of its type and genre, whether visual or written. Methods: The tested hypothesis is that the nature of systems strictly determines the nature of the signifier and the signified with which we deal at the level of aesthetic appreciation of the elements of the cosmic environment within our limits of perception. Therefore, the research uses the general systemic analysis methodology within the bounds of interpretation, benefiting from some approaches of aesthetic criticism. Results:.The duality of (text – sign) governs the interpretive systems of culture. We cannot understand meaning without signs; the logos is the father who monitors the waywardness of writing, as Derrida explained in his scholarly project. Through the philosophical aesthetic analysis of the poetic text in particular, this was largely confirmed. The aesthetic experience is summarized in the transition from meaning to impact or effect. Conclusions: The systems of signs are part of the systems of the universe and the structural order of its entities; signs are the mental means for modeling and framing things in a way that the brain can handle in terms of encoding and decoding. The search for the aesthetics of meaning and its impact is a search within the signs.